Species richness both impedes and promotes alien plant invasions in the Brazilian Cerrado - Lannes, Luciola S. [UNESP]; Karrer, Stefanie; Teodoro, Danielle A. A.; Bustamante, Mercedes M. C.; Edwards, Peter J.; Olde Venterink, Harry (Springer Nature, 2020)
Worldwide, alien plant invasions have been intensively studied in the past decades, but mechanisms controlling the invasibility of native communities are not fully understood yet. The stochastic niche hypothesis predicts that species-rich plant communities are less prone to alien plant invasions than species-poor communities, which is supported by some but not all field studies, with some very species-rich communities such as the Brazilian Cerrado becoming heavily invaded. However, species-rich communities potentially contain a greater variety of facilitative interactions in resource exploitation than species-poor communities, from which invasive plants might benefit. This alternative hypothetical mechanism might explain why nutrient-poor, species-rich ecosystems are prone to invasion. Here we show that a high species richness both impedes and promotes invasive plants in the Brazilian Cerrado, using structural equation modelling and data from 38 field sites. We found support for the stochastic niche hypothesis through an observed direct negative influence of species richness on abundance of alien invasive species, but an indirect positive effect of species richness on invasive alien plants through soil phosphatase activity that enhances P availability was also found. These field observations were supported with results from a mesocosm experiment. Root phosphatase activity of plants increased with species richness in the mesocosms, which was associated with greater community P and N uptake. The most prominent alien grass species of the region, Melinis minutiflora, benefited most from the higher N and P availability in the species mixtures. Hence, this study provides a novel explanation of why species-richness may sometimes promote rather than impede invasion, and highlights the need to perform facilitation experiments in multi-species communities.